2010
DOI: 10.1667/rr1832.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of56Fe-Particle Radiation-Induced Alterations in the Rat Brain: Magnetic Resonance Imaging and Histological Assessments

Abstract: 56Fe-particle radiation-induced brain disturbances are a major health concern for astronauts during long-term space travel. The present study investigated temporal modifications within the brain after 56Fe-particle exposure using in vivo magnetic resonance imaging (MRI) correlated to histology. Male Sprague-Dawley rats were exposed to brain-only 56Fe-particle radiation. MRI including T2-weighted, diffusion-weighted, pre/postcontrast enhanced T1-weighted imaging was performed 0.25-18 months after exposure. T2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…Lower MD has been related to higher cell density in tumours (Chenevert et al, 2006;Gibbs et al, 2009). Moreover, a recent study in rats found that over an 18-month period after radiation treatment temporal changes in ADC were negatively correlated with changes in glial cell staining in the hippocampus (Huang et al, 2010). Although MD does not measure cell density directly, these findings suggest that differences in neuronal and glial cell densities may contribute to the observed neostriatal effects in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…Lower MD has been related to higher cell density in tumours (Chenevert et al, 2006;Gibbs et al, 2009). Moreover, a recent study in rats found that over an 18-month period after radiation treatment temporal changes in ADC were negatively correlated with changes in glial cell staining in the hippocampus (Huang et al, 2010). Although MD does not measure cell density directly, these findings suggest that differences in neuronal and glial cell densities may contribute to the observed neostriatal effects in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…beams were horizontal. The proton and 56 Fe dosimetry was calculated at the NSRL and has been described in detail earlier (Tucker JD et al 2004, Huang L et al 2010, Peng Y et al 2009, Obenaus A et al 2008). To ensure constant LET values, mice were exposed at the entrance plateau region of the Bragg curve of the beam and beam uniformity (±2%) across the exposure field was calculated by densitometric analysis of exposure images obtained from NSRL Physics laboratory and analyzed using ImageJ v1.45g software.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also shown that exposing young animals to HZE particle radiation results in "accelerated aging" (Joseph et al, 1992;Poulose et al, 2011), a process where young animals exhibit behavioral and molecular changes similar to that of aged animals. Most of the studies support the role of OS and inflammation as mediators of the deficits observed in neuronal and cognitive functioning following exposure to HZE radiation; however, recent studies conclude that HZE radiation not only causes OS and inflammation, but also alters protective signaling, thereby unleashing a cascade of detrimental signals which ultimately leads to the death of neurons (Cherry et al, 2012;Huang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%